Validation of single measurement of 12-hour urine excretion for estimation of sodium and potassium intake. A longitudinal study - Molina, Maria del Carmen Bisi; Pereira, Taísa Sabrina Silva; Porto, Aline Silva; Silva, Raiane PereiraSilva; Santana, Nathália Miguel Teixeira; Cade, Nágela Valadão; Mill, José Geraldo (São Paulo Medical Journal, 2018)
BACKGROUND: Evaluation of sodium and potassium intake can be carried out using different methods. Biological markers are able to capture intra and inter-individual variability and are used as separate measurements of consumption. The aim of this study was to test the validity of a single measurement of urinary sodium and potassium excretion as representative of habitual intake. DESIGN AND SETTING: Longitudinal study, federal university. METHODS: Food consumption data from a sample of adult university students and public servants (25 to 74 years old) were collected through 24-hour records and 12-hour urinary sodium and potassium excretion at five different times over a one-year period. The dietary data were entered into a nutritional research data software system and the sodium and potassium intakes were estimated. The variables were tested for normal distribution using the Kolmogorov-Smirnov test. One-way analysis of variance or the Kruskal-Wallis test was used to evaluate means. Correlations between measurements using Pearson or Spearman coefficients were calculated. The degree of agreement between the five measurements was given by the intraclass correlation coefficient. RESULTS: Satisfactory agreement was found between the five measurements of urinary sodium and potassium excretion over a year, with little variability in consumption. CONCLUSION: A single measurement of urinary sodium and potassium accurately estimated the usual average consumption of these electrolytes. This can be used in population-based studies.